Cellular Senescence-Related Genes: Predicting Prognosis in Gastric Cancer - Dai, Longfei; Wang, Xu; Bai, Tao; Liu, Jianjun; Chen, Bo; Yang, Wenqi (Frontiers in Genetics, 2022)
Our study aimed to explore the effect of cellular senescence and to find potential therapeutic strategies for gastric cancer. Cellular senescence-related genes were acquired from the CellAge database, while gastric cancer data were obtained in GEO and TCGA databases. SMARCA4 had the highest mutation frequency (6%), and it was linked to higher overall survival (OS) and Progression-free survival (PFS). The gastric cancer data in the TCGA database were served as a training set to construct a prognostic risk score signature, and GEO data were used as a testing set to validate the accuracy of the signature. Patients with the low-risk scores group had a longer survival time, while the high-risk scores group is the opposite. Patients with low-risk scores had higher immune infiltration and active immune-related pathways. The results of drug sensitivity analysis and the TIDE algorithm showed that the low-risk score group was more susceptible to chemotherapy and immunotherapy. Most patients with mutation genes had a lower risk score compared to wild type. Therefore, the risk score signature with cellular senescence-related genes can predict gastric cancer prognosis and identify gastric cancer patients who are sensitive to chemotherapy and immunotherapy.